A locally convergent continuous-time algorithm to find all the roots of a time-varying polynomial - Menini, Laura; Possieri, Corrado; Tornambè, Antonio (Automatica (Oxford), 2021)
In this technical communique, a locally convergent continuous-time model for the Durand–Kerner method is proposed to simultaneously determine all the roots of a time-varying polynomial. The effectiveness of this method is demonstrated through its application to a benchmark example.